Problematika Pembelajaran Balaghah: Mahasiswa Semester VI Program Studi Pendidikan Bahasa Arab di STAI Nurul Iman Parung, Bogor - Parhan, Parhan; Isyanto, Nur (STAINI Press, 2025)
The teaching of balaghah in the department of Arabic language education in private Islamic tertiary institutions with different quality, student input and geographical location from the department of Arabic language education in public Islamic tertiary institutions is a challenge in itself because learning balaghah cannot be separated from the science of Arabic, especially nahwu and sharaf to minimise learning difficulties and facilitate understanding. This study aims to discuss more deeply the problems of teaching balaghah in the Arabic language education department atSTAI Nurul Iman Parung, Bogor. By using a qualitative approach, and data collection using observation, interviews and documentation. The results of the study concluded that there are several main problems in teaching balaghah in the Arabic Language Education Study Programme of STAI Nurul Iman Parung, Bogor. Some of the factors that contribute to this problem are the heterogeneity of students' educational background, low motivation to learn, ineffective teaching methods, and lack of library resources. Therefore, improvements in teaching approach, selection of more effective methods, and increased access to relevant literature sources are needed to improve the quality of balaghah teaching in the study programme.